Adverse Cardiovascular Events after a Venomous Snakebite in Korea - Kim, Oh Hyun (Yonsei Med J, 2016)
PURPOSE: Although cardiac involvement is an infrequently recognized manifestation of venomous snakebites, little is known of the adverse cardiovascular events (ACVEs) arising as a result of snakebite in Korea. Accordingly, we studied the prevalence of ACVEs associated with venomous snakebites in Korea and compared the clinical features of patients with and without ACVEs. MATERIALS AND METHODS: A retrospective review was conducted on 65 consecutive venomous snakebite cases diagnosed and treated at the emergency department of Wonju Severance Christian Hospital between May 2011 and October 2014. ACVEs were defined as the occurrence of at least one of the following: 1) myocardial injury, 2) shock, 3) ventricular dysrhythmia, or 4) cardiac arrest. RESULTS: Nine (13.8%) of the 65 patients had ACVEs; myocardial injury (9 patients, 13.8%) included high sensitivity troponin I (hs-TnI) elevation (7 patients, 10.8%) or electrocardiogram (ECG) determined ischemic change (2 patients, 3.1%), and shock (2 patient, 3.1%). Neither ventricular dysrhythmia nor cardiac arrest was observed. The median of elevated hs-TnI levels observed in the present study were 0.063 ng/mL (maximum: 3.000 ng/mL) and there was no mortality in the ACVEs group. Underlying cardiac diseases were more common in the ACVEs group than in the non-ACVEs group (p=0.017). Regarding complications during hospitalization, 3 patients (5.4%) in the non-ACVEs group and 3 patients (33.3%) in the ACVEs group developed bleeding (p=0.031). CONCLUSION: Significant proportion of the patients with venomous snakebite is associated with occurrence of ACVEs. Patients with ACVEs had more underlying cardiac disease and bleeding complication.